Instructional Competencies Required by Technical College Teachers for Effective Performance in Technical Drawing - Shola F, Bakare; Abdul Latib, Azlan; Kamin, Yusri; Sukri Saud, Muhammad; Fadila Amin, Nor (International Journal of Engineering and Technology, 2018)
The National Business and Technical Education Board (NABTEB) chief examiners reported that instructors employed to teach the students lack the required competencies in teaching methods in Technical Drawing (TD), which leads to poor performance. Therefore, a study was conducted to identify the instructional competencies required by technical college teachers in teaching TD. To achieve this objective, 3 (three) research questions were formulated to guide the study. The population of the study comprised 103 technical college teachers in Ondo state, Nigeria. A structured questionnaire of 38 items was used for data collection. The instrument was face validated by 3 (three) experts. Mean and standard deviation was used to answer the research questions and the reliability of the instrument was also established using Cronbach’s Alpha, with the reliability coefficient being 0.84. Based on the findings, it was determined that technical college teachers required the identified 15 instructional competencies to teach effectively. It was also found that there are factors that militate against the teachers’ competencies. The study’s findings contributed to identifying these factors and to how the competencies could be enhanced.